Pathological and morphological properties of chronic gastroduodenitis in children with connective tissue dysplasia - O. M. Mukvich; T. D. Zadorozhnaja; O. V. Lavrenchuk; T. N. Archakova (Zaporozhye State Medical University, 2018)
Abstract Collagen metabolic disorder affects morphological changes of mucosal-cellular barrier determining clinically-aided reparation processes. Morphologic assessment enables personalized approaches to handle inflammatory processes in upper gastro-intestinal tract (GIT) associated with extracellular matrix disorders. Aim: examining patho-morphologic properties of gastric and duodenal mucosa in children with CGD associated with CTD. Materials and methods. Morphologic examination of endoscopic biopsies in 63 children, 11-17 years old. Samples were processed by hematoxylin eosin section staining. The influence of dysplasia and patient's response to standard therapy on morphological changes were assessed using odd ratio statistics, confidence limits, and p-values. Results. Dependency of morphological changes versus the CTD degree and patient response to standard therapy: foci of fibrosis OR=7 and 5,25, eosin infiltration OR=3,684 and 3,667, dystrophic epithelium changes OR=2,344 and 3,023, change in glands architectonics OR=3,684 and 3,279, respectively. Biopsy samples from patients with CTD and weak therapy response feature dense lymphocyte-plasmocyte infiltration of gland epithelium and lamina propria (81,3%), pronounced diffuse edema (68,8%), and uneven gland localization with changed architectonics and dystrophically modified epithelium (62,5%). 78,6% not therapy-responsive children without DCT have morphologically pronounced CGD whereas irresponsiveness in children with the associated pathology isn't strongly connected with CGD morphology. Conclusion. Gastric and duodenal mucosa inflammation in children with expressed CTD features are characterized with lympho-histological infiltration of lamina propria and surface gland epithelium, increased edema, dystrophic changes of gland epithelium, and spread fibrosis loci indicating high risk of early chronicity and atrophic process formation. The account of clinical CTD conditions affecting pathogenic mucosal processes stipulates adequate CGD development assessment.